Neuroprotective effect of Betalain against AlCl3-induced Alzheimer's disease in Sprague Dawley Rats via putative modulation of oxidative stress and nuclear factor kappa B (NF-κB) signaling pathway - Shunan, Di; Yu, Miao; Guan, Huibo; Zhou, Yanyan (Biomedicine & pharmacotherapy, 2021)
Alzheimer's disease (AD) is the most progressive form of neurodegenerative disease, which severely impairs cognitive function. Oxidative stress is identified to contribute to the mechanisms responsible for the pathogenesis of such neurodegenerative diseases. Aluminum is a potent neurotoxin for inducing oxidative stress associated with neurodegenerative diseases. The treatment for AD is limited; hence more treatment options are the need of the day. Betalain is known for its multitude of medicinal assets, including anti-inflammatory activity. Hence, this study was intended to investigate the possible protective effect of betalain against aluminum chloride (AlCl3) induced AD on Sprague Dawley (SD) rats. AlCl3 (100 mg/kg) was administrated orally to induce the AD in SD rats. The rats were supplemented with low and high betalain doses (10 mg/kg and 20 mg/kg) for four weeks. At the end of the experiment, the rats were subjected to behavioral examination and sacrificed to study the biochemical and histological parameters. The results showed attenuation of memory and learning capacity, suppression of lipid oxidation (MDA) through regulation of antioxidant content (SOD, CAT, and GSH) and inhibition of lactate dehydrogenase (LDH), nitric oxide (NO), acetylcholinesterase (AChE), and transmembrane protein (Na+K+ATPase) activity. In addition, the NF-ƙB associated mRNA expression (TNF-α IL-6, Il-1β, iNOS, COX-2) was decreased, as evidenced in histopathological results. The present investigation established that the betalain treatment ameliorated the AlCl3 induced AD by modulating NF-κB pathway activation.